First microscopic, pathological, epidemiological, and molecular investigation of Leucocytozoon (Apicomplexa: Haemosporida) parasites in Egyptian pigeons - Elshahawy, Ismail Saad; Mohammed, Eman Sayed; Mawas, Amany Sayed; Shibat El Hamd, Dina M. W.; Ali, Esraa; Alghamdi, Abeer M.; Alzaylaee, Hind; Elmahallawy, Ehab Kotb (Frontiers in Veterinary Science, 2024)
Introduction: Leucocytozoon is an intracellular blood parasite that affects various bird species globally and is transmitted by blackfly vectors. This parasite is responsible for leucocytozoonosis, a disease that results in significant economic losses due to reduced meat and egg production. There is limited knowledge about the epidemiological pattern of leucocytozoonosis and its causative species in Egypt, particularly in pigeons. Methods: The current study involved the collection of 203 blood samples from domestic pigeons from various household breeders and local markets across Qena Province, Upper Egypt. Samples were initially examined for potential Leucocytozoon infection using blood smears, followed by an evaluation of associated risk factors. Molecular identification of the parasite in selected samples (n=11), which had initially tested positive via blood smears, was further refined through nested PCR and sequence analysis of the mitochondrial cytochrome b gene to ascertain the Leucocytozoon species present. Additionally, histopathological examination of the liver, spleen, and pancreas was conducted on animals that tested positive by blood smears. Results: Interestingly, 26 out of 203 samples (12.08%) had confirmed Leucocytozoon infections based on microscopic analysis. Additionally, all 11 samples that initially tested positive via blood smears were confirmed positive through nested PCR analysis, and their sequencing revealed the presence of Leucocytozoon sabrazesi, marking the first report of this parasite in Egypt. The study into potential risk factors unveiled the prevalence of Leucocytozoon spp. seems host gender-dependent, with males exhibiting a significantly higher infection rate (33.33%). Additionally, adult birds demonstrated a significantly higher infection prevalence than squabs, suggesting an age-dependent trend in prevalence. Seasonality played a significant role, with the highest occurrence observed during summer (37.25%). Histopathological examination revealed the presence of numerous megaloschizonts accompanied by lymphocytic infiltration and multiple focal areas of ischemic necrosis. Conclusions: To our knowledge, this is the first study to shed light on the epidemiological characteristics and molecular characterization of leucocytozoonosis in pigeons in Egypt. Further research endeavors are warranted to curb the resurgence of Leucocytozoon parasites in other avian species across Egypt, thereby refining the epidemiological understanding of the disease for more effective control and prevention measures.